137Cs and 40K concentration ratios (CRs) in annual and perennial plants in the Caspian coast. (September 2019) - Abbasi, Akbar; Mirekhtiary, Fatemeh
Abstract: This research attempted to investigate the plant/soil concentration ratios (CRs) of 137 Cs and 40 K in plants that grow on the Anzali Lagoon of the Caspian coast, Iran. The activity concentrations of 137 Cs and 40 K were measured in soil samples, annual plants ( Echinochloa crus-galli, Digitaria sanguinalis, and Trifolium repens ), and perennial plants ( Phragmites australis, and Cynodon dactylon ). The relationship of activity concentration with soil particle density, and pH of soil samples, CR, and 137 Cs/ 40 K discrimination factor (DF) were determined. The activity concentration of 137 Cs in the soil, annual plants, and perennial plants ranged between 12- and 124 (Bq/kg dry weight), 2- and 17 (Bq/kg dw), and 2 - and 14 (Bq/kg dw), respectively. The geometric mean (GM) values of DF in annual and perennial plants were 0.57 and 0.55, respectively. The CR for 137 Cs and 40 K varied as a non-linear relation in annual plants and perennial plants. This study showed that the CRs for 137 Cs in annual plants were higher than the CRs for perennial plants. Graphical abstract: Unlabelled Image Highlights: Calculation of 137 Cs and 40 K activity concentration in soil and plant species Evaluation of 137 Cs/ 40 K discrimination factor (DF) in plant species Calculation the concentration ratios (CRs) of 137 Cs and 40 K in plant species Comparison of 40 K and 137 Cs CR in annual plant and perennial plant species